2013 IEEE/ASME International Conference on Advanced Intelligent Mechatronics 2013
DOI: 10.1109/aim.2013.6584241
|View full text |Cite
|
Sign up to set email alerts
|

Parameter identification study of frequency response data for a trilayer conjugated polymer actuator displacement model

Abstract: This article investigates the effect of three uncertain parameters on a model of conjugated polymer actuators. These uncertain parameters are the diffusion coefficient (D), the resistance (R), and the double-layer WKLFNQHVV / 7KH PRGHO VHQVLWLvity to these parameters is analyzed and a parameter estimation study is performed using artificially generated data as well as laboratory yielded experimental measurements. The parameter estimation method used in this article is based on a Bayesian cost function, and giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…From the sensitivity analysis it was concluded that C d affects the behaviour of equation ( 9) more than D. In contrast the diffusion coefficient D shows signs of non-identifiability, which is coherent with the implications from the sensitivity analysis, which is not displayed here for the sake of brevity (similar sensitivity analyses can be found in [17,24]). The sensitivity analysis shows that C d is the most influential parameter on the shape of the Bode plots.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…From the sensitivity analysis it was concluded that C d affects the behaviour of equation ( 9) more than D. In contrast the diffusion coefficient D shows signs of non-identifiability, which is coherent with the implications from the sensitivity analysis, which is not displayed here for the sake of brevity (similar sensitivity analyses can be found in [17,24]). The sensitivity analysis shows that C d is the most influential parameter on the shape of the Bode plots.…”
Section: Resultssupporting
confidence: 75%
“…Nguyen et al [13,16] has estimated the change of parameters with respect to the applied voltage. Blanchard et al [17] investigated the effect of uncertain parameters for the model used in [16] and compared the parameter estimation results for the full model used in [16] with its reduced model introduced in [16]. Previously, the diffusion coefficient is assumed not to have much effect on the cost function.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated values of the parameters used in the model are listed in table 1. The diffusion coefficient D is an uncertain parameter in the model with an expected range of 1 × 10 −14 to 2 × 10 −10 m 2 s −1 [32]. This coefficient tends to decrease as the solvent evaporates.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, between 2007 and 2021, many infrastructure developments happened in Kenya, affecting Kenya industrial exports to the EAC. The introduction of flagship projects such as the Standard Gauge Railway (SGR) in 2013, Mombasa Port Modernization (2015, the Lamu Port-South Sudan-Ethiopia-Transport (LAPSSET) project (March 2012), and airport and airstrip rehabilitation ( 2015) have all had a significant impact on the ease of trade and goods flow to other EAC countries. The six countries of EAC are the target for study because of their proximity to each other, such that their cross-border trade can be quantified, for example the Uganda market so big that most goods from Kenya go to Uganda.…”
Section: Scope Of the Studymentioning
confidence: 99%